Ukrainian agricultural labour potential management modelling in the context of European integration : ст. - Vasylchak, S. et. al.; Soloviy, S. (University of Economics and Technology ; Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2023)
Research related to the labour potential in agriculture is relevant as the agricultural sector is one of the key sectors of the economy of Ukraine, and the integration of the country into the EU opens up new opportunities and requires the appropriate adaptation of management approaches to achieve competitiveness and sustainable development in the field of agricultural activity. The study aims to analyse, develop, and improve already existing strategic approaches to the management of the labour potential of Ukraine in agriculture, addressing the processes of integration into the European Union. Analytical, statistical, functional, system analysis, deduction, synthesis, and comparison methods were used in the study. The state of labour potential in agriculture was analysed, assessing the qualitative and quantitative composition of employees, their skills and education. The influence of European integration on the agricultural sector, in particular its requirements and opportunities for development, was studied, and a model of management and development of labour potential for the effective functioning of agrarian business was developed. The application of the strategy at the agricultural enterprise AgroGeneration was modelled. Working conditions and social protection of workers were studied, prioritizing the formation and development of personnel potential in the agricultural sector. The study determined that the management of labour potential in agriculture involves the use of a comprehensive strategy that would include industry specifics, European standards, innovative approaches, and best practices of other countries. The practical significance of the study lies in the development of specific practical recommendations and strategies for management bodies, agricultural enterprises, as well as agricultural workers to optimize the use of labour potential.
Keywords: agricultural labour potential management; управління сільським господарством